Presentation and management of gastrointestinal stromal tumours. - REYNOLDS, JOHN; MULDOON, CIAN; RAVI, NARAYANASAMY (My University, 2013)
Duodenal gastrointestinal stromal tumors (GIST) have been described primarily in isolated case reports. In order to learn more about duodenal GIST, a retrospective review of patients with GIST managed at a single institution between 2000 and 2005 was conducted. Thirty-eight GIST of the stomach and small bowel were analyzed. Eight (21%) were duodenal GIST. The median size of duodenal GIST (6.0 cm) and small bowel GIST (6.3 cm) was larger than the median size of gastric GIST (3.0 cm). The most common presentation of duodenal GIST was bleeding (50%) which was similar to other small bowel GIST (49%) but different from gastric GIST which were most commonly an incidental finding (62%). Two patients (25%) with duodenal GIST had a history of neurofibromatosis. The duodenal GIST were located in the 2nd (n = 5, 63%) and 3rd portion of duodenum (n = 3, 37%). Seven of 8 patients underwent complete resection of duodenal GIST. Pancreaticoduodenectomy was the most common operation performed (n = 5); 2 patients were treated with partial duodenal resection. No patients undergoing pancreaticoduodenectomy (n = 5) were found to have lymph node metastases. No patients received neo-adjuvant or adjuvant therapy with Imatinib. Following resection, 2 patients have recurred (12 and 48 mo.), 4 patients are without disease (1, 6, 6, and 24 mo.), 1 patient died postoperatively. Duodenal GIST are relatively rare tumors that present most commonly with gastrointestinal bleeding. Duodenal GIST are associated with neurofibromatosis. Many duodenal GIST require pancreaticoduodenectomy for complete removal.
PUBLISHED
Keywords: Duodenal gastrointestinal stromal tumors (GIST)